Impact of a Modified Polyurea Coating on the Chemical and Microbiological Quality of Drinking Water: A Preliminary Study - Przybecki, Artur; Kruszelnicka, Izabela; Ginter-Kramarczyk, Dobrochna; Motylski, Marcin (Instal, 2026)
This study presents findings on the chemical and microbiological safety of the polyurea-based composite coating, designed for renovating potable water pipelines. Tests were performed in line with European standards PN-EN 12873-1, PN-EN 14395-1, and PN-EN 16421. The research examined metal, organic compound, and primary aromatic amine migration, along with organoleptic and microbiological water quality after contact with the coating. No regulatory limits were exceeded, and PAAs were below the detection threshold of 0.001 mg/L. These results demonstrate that COVERLAN does not adversely impact drinking water quality and is safe for use in internal pipeline rehabilitation.